EKSISTENSI PENDIDIKAN KARAKTER BERBASIS LOCAL WISDOM - I PUTU SUARDIPA (Purwadita : Jurnal Agama dan Budaya, 2018)
Building education in schools through local wisdom contains relevant and useful values for education. Therefore, local wisdom-based education can be done by revitalizing the local culture. To realize an advanced and dignified Indonesian state because it has a high value as a cultural characteristic literacy. The development of character education in schools through local wisdom contains relevant and useful values for education. Therefore character education based on local wisdom can be done by revitalizing local culture. To realize character education in schools based on local wisdom requires understanding, understanding, awareness, cooperation, and participation of all elements of the learning community. In this case should the stakeholders in the world of education should be biased to instill the character early on the students / learners to form the generation of lovers of local wisdom and love the nation. Character education based on local wisdom should be started from child born through family, to preserve the root of culture that refers to the individual’s love for his nation